Uma crítica à lógica do capital da sociedade de consumo contemporânea: a contribuição da psicanálise lacaniana na perspectiva de Slavoj i ek - Dias, Brendali (2010)
This project aims to criticize the logic of the consumption capitalism in the contemporary society. Our criticism takes as its major premise the harmfulness of the way this logic is kept through the promise of completeness and foreclosure of object a. The research was developed as from the Lacanian psychoanalytic theory based on Slavoj i ek, which makes use of it to propose a critical social and political theory against the dictates of the logic of capital. i ek points out that the logic of capital keeps itself as from a proposal which takes the subject to consider that it is impossible to escape this logic and with that becomes conniving with it to face the consumption as the only way to calm his/her afflictions. As a result of this pursuit to calm his/her afflictions, the subject is seduced by the promise of completeness, facing the offers for objects/goods as a way to feel welcomed by social through them, consuming indiscriminately. Based on i ek s arguments, who uses as a base for his criticism the Lacanian psychoanalytic theory, we discuss the place of the subject in this logic, and his/her alternatives to escape from it. We put in doubt the consumerism in capitalism, raising the inquiry about why the subject places himself/herself in such a complacent way towards this logic. We reflect, yet, on the use made by the capitalist system of the technologies associated to science, which have been presented by the media as capable of generating in subject a completeness state, which is never found, leading the society to severe pathologies. These pathologies, faced as symptom by psychoanalysis, are pointed out as rebellion against this logic. The symptom, therefore, manifests itself as a way for the subject to show his/her dissatisfaction with the logic of capital, being also the chance for the subject to escape from it. Finally, we introduce i ek s proposal to bring a political position of the subject against the impossible of the logic of capital to enable alternatives which turn possible escaping from this logic, placing the need to risk the impossible beyond the imposed by the logic of capital